Surface Wave Isotropic and Azimuthally Anisotropic Dispersion Across Alaska and the Alaska‐Aleutian Subduction Zone. Issue 11 (25th November 2022) - Liu, Chuanming; Zhang, Shane; Sheehan, Anne F.; Ritzwoller, Michael H.
Abstract: Comprehensive observations of surface wave anisotropy across Alaska and the Aleutian subduction zone are needed to improve understanding of its tectonics, mantle dynamics, and earthquake risk. We produce such observations, using stations from the USArray Transportable Array and regional networks across Alaska and the Alaska Amphibious Community Seismic Experiment in the Alaska‐Aleutian subduction zone both onshore and offshore. Our data include Rayleigh and Love wave phase dispersion from earthquakes (28–85 s) and ambient noise two‐ and three‐station interferometry (8–50 s). Compared with using two‐station interferometry alone, three‐station interferometry significantly improves the signal‐to‐noise ratio and approximately doubles the number of measurements retained. Average differences between both isotropic and anisotropic tomographic maps constructed from different methods lie within their uncertainties, which is justification for combining the measurements. The composite tomographic maps include Rayleigh wave isotropy and azimuthal anisotropy from 8 to 85 s both onshore and offshore, and onshore Love wave isotropy from 8 to 80 s. In the Alaska‐Aleutian subduction zone, Rayleigh wave fast directions vary from trench parallel to perpendicular and back to parallel with increasing periods, apparently reflecting the effect of the subducted Pacific Plate. The tomographic maps provide a basis for inferring the 3‐D anisotropic crustal and uppermost mantle structure across Alaska and the Aleutian subduction zone. Plain Language Summary: We construct a new database across continental Alaska and the Alaska‐Aleutian subduction zone of directionally dependent measurements of the speed of seismic surface waves. The application of a new method in which observations at three stations at a time are considered improves the number and quality of measurements. Our results resolve the local directional‐dependence of seismic wave speeds (anisotropy) and in many cases, are directly related to known geological structures in the earth's crust and upper mantle. The complicated anisotropy beneath the Alaska‐Aleutian subduction zone reflects the complex tectonic environment in this region. This study provides the basis for constructing a 3D seismic model of anisotropy beneath Alaska and the subduction zone. Key Points: An isotropic and anisotropic surface wave dispersion database across Alaska is constructed for Rayleigh and Love waves from 8 to 85 s Three‐station direct‐wave interferometry greatly improves the number and quality of measurements compared to two‐station interferometry The Rayleigh wave azimuthally anisotropic pattern beneath the Alaska‐Aleutian subduction zone reflects the effect of the subducting slab